Predictive value of melatonin and serotonin levels in early recovery period of cerebral ischemic hemispheric stroke - S. O. Medvedkova (Zaporozhye State Medical University, 2017)
The aim was developing of criteria for prediction of the early recovery period outcome of cerebral ischemic hemispheric stroke (CIHS) on the base of the identification of serum concentration of melatonin and plasma level of serotonin. Materials and methods: complex clinical and paraclinical investigation was carried out in 77 patients (the average age of patients was 57.9 ± 0.9 years) on early recovery period of CHIS using of clinical scales (National Institute of Health Stroke Scale, Barthel Index, modified Rankin Scale) on the 10th, 30th, 90th and 180th day of disease, and visualization of cerebral structures by CT scan, and identification of the serum concentration of melatonin and serotonin plasma level on the 10th, 30th day of disease, and also by the calculation of the melatonin/serotonin ratio (MSR) as serum concentration of melatonin divided by serotonin plasma level. Results. Using the comparative ROC-analysis it was defined that the most informative parameters for prediction of moderate and severe disability as for value according to mRS ≥ 3 points on the 180th day are the level of MSR on the 30th day (AUC = 0.78, p < 0.05), serotonin plasma level on the 30th day (AUC = 0.74, p < 0.05), dynamics of serum concentration of melatonin on the 30th day (AUC = 0.67, p < 0.05), dynamics of serotonin plasma level on the 30th day (AUC = 0.67, p < 0.05), dynamics of MSR on the 30th day (AUC = 0.66, p < 0.05) and serum concentration of melatonin on the 30th day (AUC = 0.66, p < 0.05). Conclusions. The level of MSR ˃212,0 on the 30th day was the predictor of moderate and profound disability for modified Rankin's scale ≥3 points on the 90th (AUC = 0.81, p ˂ 0.05; sensitivity = 100.0 %, specificity = 75.0 %) and on the 180th day of disease was (AUC = 0.78, p ˂ 0.05; sensitivity = 100.0 %, specificity = 73.3 %); the serotonin plasma level ≤0.15 mcmol/l on the 30th day of CIHS was the predictor of moderate and profound disability for modified Rankin's scale ≥3 points on the 180th day of disease (AUC = 0.74, p ˂ 0.05; sensitivity = 60.0 %, specificity = 86.7 %).